Sensorineural Hearing Loss and its Management through Ayurveda – A Case Study - Sultana, K J Najma; Rathi, S (International Research Journal of Ayurveda & Yoga, 2022)
Hearing is one of the primary modes of communication. Hearing loss is one of the most common sensory deficit and it comprises a broad spectrum of clinical presentations. Impairment of hearing occurs when there is inability for sounds to be transmitted through or interpreted by our brain. Disorders of internal ear and auditory nerve will lead to sensorineural hearing loss (SNHL). The management of the SNHL is conventionally with rehabilitation with hearing aids and cochlear implants, and the option for pharmacologically treating the hearing impairment is limited. Hence there is need to lookback to our classical methods as told by our Acharyas for treating SNHL. In Ayurveda, hearing loss can be correlated to badhirya, wherein many therapeutic procedures, formulations have been told by our acharyas for the successful management of badhirya. So in the present case an attempt is made to treat a case of SNHL through ayurveda treatment strategy.